Comparative chloroplast genomes and phylogenetic analysis of the Phlegmariurus (Lycopodiaceae) from China and neighboring regions - Ruichen Xiang; Ruichen Xiang; Ruichen Xiang; Jiayu Hu; Jiayu Hu; Javzandolgor Chuluunbat; Javzandolgor Chuluunbat; Javzandolgor Chuluunbat; Javzandolgor Chuluunbat; Fei Wu; Fei Wu; Bo Qin; et al. (Frontiers in Plant Science, 2025)
The lycophyte genus Phlegmariurus (Herter) Holub (Huperzioideae, Lycopodiaceae) is ecologically and pharmaceutically significant, notably as a natural source of Huperzine A—a promising therapeutic candidate for Alzheimer’s disease. Despite its medicinal potential, taxonomic ambiguities on species delimitation and infrageneric classification have impeded conservation and sustainable utilization efforts. Here, we assembled 40 Phlegmariurus complete chloroplast genomes, including all taxa from China, most of which were reported for the first time. Our results revealed the conserved quadripartite architectures and little variation in genome size and GC content in the genus. Comparative analyses on genome sequences identified seven hypervariable loci as prospective DNA barcodes for species discrimination. The phylogenetic toopologies reconstructed from nuclear ribosomal DNA and chloroplast genome data consistently resolved four monophyletic clades, further validated by SNP-based discriminant analysis of principal components. They are well corresponding to the four sections’ classification on Chinese taxa (sect. Squarrosurus, sect. Phlegmariurus, sect. Fargesiani, sect. Hamiltoniani). Notably, nuclear and chloroplast data congruently yielded a sister relationship between sect. Squarrosurus and sect. Phlegmariurus. However, the phylogenetic positions of sect. Fargesiani and sect. Hamiltoniani conflicted across different datasets. The diversification of the Chinese Phlegmariurus was traced back to the Oligocene (ca. 26.04 Ma). The comprehensive genetic resources generated herein provide a foundation for future research on species identification, population genomics and genetic diversity preservation in this medicinally significant vital genus.